German economy: Strong employment growth, weak investment activity - Ferdinand Fichtner; Karl Brenke; Marius Clemens; Simon Junker; Claus Michelsen; Thore Schlaak; Kristina van Deuverden (DIW Economic Bulletin, 2017)
The German economy's upward growth trend continues, with the economic output expected to increase by 1.4 percent this year with slightly overloaded capacities. Employment growth remains strong with the creation of 600,000 new jobs, which has in turn led to an increase in private consumption - one of the key growth drivers of the German economy. The higher inflation rates are dampening purchasing power, but they will subside later on in the forecast period. The high public budget surpluses will experience a sharp decline. Investment, on the other hand, remains weak, partially due to the fact that Brexit and Trump are creating uncertainty for German exporters. Frictions in the financial markets that may arise as a result of the upcoming elections - in France and the Netherlands, for example - could present risks for the real economy.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook